Polyoxoanions assembled by the condensation of vanadate, tungstate and selenite: solution studies and crystal structures of the mixed metal derivatives (NMe4)2Na2[WVI4VV2O19]·8H2O and (NMe4)4.83[(SeIV WVI4.57VV4.43O33)2(WVI(O)(H2O))(VVO)2.6]·10.57H2O. (30th June 2015) - Abramov, Pavel A.; Peresypkina, Eugenia V.; Izarova, Natalia V.; Vicent, Cristian; Zhdanov, Artem A.; Kompankov, Nikolay B.; Gutsul, Tatiana; Sokolov, Maxim N.
Abstract : The reaction of SeO3 2− /WO4 2− /VO4 3− gives a complex mixture of Lindqvist W–V anions and larger Se–W–V containing POMs. Abstract : The reaction of acidified aqueous solutions of Na2 WO4, NaVO3 and SeO2 in a 16 : 4 : 3 molar ratio gives a complex mixture of polyoxometalates (POMs) with both W VI and V V addenda, formulated as [(Se IV W VI x V V 9− x O33 )2 (W VI O(H2 O))(VO) m ] n − with x = 4, 5, 6; m = 2 or 3. In solution, the sandwich-type complexes [(Se IV W VI x V V 9− x O33 )2 (W VI O(H2 O))(VO) m ] n − slowly lose Se and convert into [W VI 4 V V 2 O19 ] 4− and further to [W VI 5 V V O19 ] 3− with a Lindqvist-type structure. These transformations were monitored with 51 V and 77 Se NMR, electrospray mass-spectrometry and capillary electrophoresis. Crystals of (NMe4 )2 Na2 [(W4 V2 )O19 ]·8H2 O (1 ) and (NMe4 )4.83 [(SeW4.57 V4.43 O33 )2 (W(O)(H2 O))(VO)2.6 ]·10.57H2 O (2 ) were isolated and structurally characterized.